Pengembangan perangkat pembelajaran materi bangun ruang sisi datar berbasis pendekatan kontekstual untuk meningkatkan kemampuan pemecahan masalah matematis siswa - Murniati, Sri; Maimunah; Roza, Yenita (Jurnal Pendidik Indonesia, 2024)
This study aims to develop contextual-based learning tools to facilitate students' mathematical problem-solving skills in the topic of Three-Dimensional Space for eighth-grade students of SMP/MTs. The developed tools include a syllabus, lesson plans, and student worksheets using the 4-D model consisting of the stages of defining, designing, developing, and disseminating. Validation results indicate that the learning tools meet the criteria of being highly valid, with an average score of 94.80% for the syllabus, 96.65% for the lesson plans, and 91.65% for the student worksheets. The validated student worksheets were tested on nine students to assess readability, resulting in an average score of 91.12%, while practicality scores were 93.30% from students and 94.13% from teachers, both categorized as highly practical. These findings demonstrate that the developed learning tools are valid, practical, and effective in facilitating students' mathematical problem-solving skills in the Three-Dimensional Space topic.